Workshop Tari Anak di SD Negeri Sudimoro 01 Kecamatan Bululawang Kabupaten Malang - Ratih Kartika Werdiningtiyas; Denna Delawanti Chrisyarani (Universitas Muhammadiyah Surabaya, 2017)
SDN Sudimoro 1 Bululawang subdistrict has not done extracurricular activities of dance art, from some guardians initiative to involve his children to follow the dance and dance arts in the local dance studio. At the time of art performances, the school finds it difficult to find a dance coach because of the lack of coaches, locations that are too far from the citizens and lack of material about children's dance. Based on the condition of SDN Sudimoro 1, it is very important to be held about dance training for elementary school students, especially low grade. This devotional activity is held five days, the first day of delivery of basic ant dance material, second day until the five participants perform the practice of motion variety of ant dance along with the floor pattern. The purpose of the workshop is to improve students' ability in maximizing the use of ant dance as a suitable learning in dance, developing and creating cultural art learning materials, especially dance art related to the concept, and improving students ability and skill.